2001
DOI: 10.3354/meps214015
|View full text |Cite
|
Sign up to set email alerts
|

First record of a fish-killing Gymnodinium sp. bloom in Kuwait Bay, Arabian Sea: chronology and potential causes

Abstract: Significant natural and aquaculture fish deaths in Kuwait Bay occurred from September to October of 1999 and were attributed to a bloom of the dinoflagellate Gymnodinium sp. A chronology of the bloom event suggests that a period of low winds and stable water-column structure preceded the bloom. Maximum cell concentrations of Gymnodinium sp. (> 6 × 10 6 cells l -1) were also immediately preceded by a more than 20-fold increase in mean inorganic nitrogen concentrations (up to 60 µM) and elevated inorganic phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 28 publications
1
72
0
Order By: Relevance
“…Spatially in the eastern part of Oman Sea, the abundance was greater in the offshore zone, while in the western region, there was a greater abundance in the coastal zone. The outbreak of Cochlodinium poykrikoides was firstly observed in offshore waters before spreading into the coastal Cochlodinium polykrikoides, which was first recorded in this study area, had been reported previously in many Asian countries such as Korea, Japan, Hong Kong, Philippine and Malaysia [15][16][17][18].…”
Section: Spatial and Temporal Distribution Of Cochlodinium Polykrikoidesmentioning
confidence: 71%
“…Spatially in the eastern part of Oman Sea, the abundance was greater in the offshore zone, while in the western region, there was a greater abundance in the coastal zone. The outbreak of Cochlodinium poykrikoides was firstly observed in offshore waters before spreading into the coastal Cochlodinium polykrikoides, which was first recorded in this study area, had been reported previously in many Asian countries such as Korea, Japan, Hong Kong, Philippine and Malaysia [15][16][17][18].…”
Section: Spatial and Temporal Distribution Of Cochlodinium Polykrikoidesmentioning
confidence: 71%
“…Moreover previous findings showed that Kuzmenko (1975), Tabassum & Saifullah (2010) observed 16 species of Chaetoceros in the month of February from Arabian Sea whereas seven species of this genus including C. lorenzianus were reported in the month of October from Kuwait Bay, Arabian Sea (Heil et al 2001). Present study manifests sporadic occurrence of the species in the month of November immediate after Tasman Spirit Oil Spill which may have attributed to the effect of oil spill in this area.…”
Section: Wwwtropicalplantresearchcom 561mentioning
confidence: 72%
“…One of the earliest anecdotal sightings was by J. M. Al-Hassan in 1981 and1982, but the first scientific study of a HAB was carried out in 1987~ 1988(Subba Rao et al, 2003. The most detailed research studies carried out specifically in Kuwait Bay were in: September ~ October 1999 (Heil et al, 2001); July 2000 (Subba Rao et al, 2003); and August ~ September 2001 . Each sighting was observed over a period of several days, and in some cases this period overlapped into the following month.…”
Section: Hab In Kuwait Watersmentioning
confidence: 99%